ISAK-based anthropometric standards for elite male and female soccer players - Petri, C.; Campa, F.; Holway, F.; Pengue, L.; Arrones, L. S. (Sports, 2024)
This study aimed to provide reference values for anthropometric characteristics of elite male and female soccer players, considering a group of individuals from the general population as controls. The anthropometric profiles of 357 elite soccer players [184 males (age 24.3 ± 4.3 y) and 173 females (age 25.2 ± 5.1 y)] participating in the first Italian league (Serie A) and 363 subjects from the general population [188 males (age 24.2 ± 4.8 y) and 175 females (age 25.0 ± 5.1 y)] were measured according to the guidelines of the International Society for the Advancement of Kinanthropometry (ISAK). Reference percentiles for stature, body mass, circumferences, eight skinfolds (biceps, triceps, subscapular, suprailiac, supraspinal, abdominal, front thigh, and calf), breadths, and somatotype were calculated and stratified by player position and sex. No difference (p > 0.05) was found in age between the two groups. Soccer players showed lower values for the sum of the eight ISAK skinfolds than individuals from the general population of the same sex. This suggests lower adipose tissue, as indicated by a lower endomorphic component. The somatotype was endomorphic mesomorph and mesomorphic endomorph for the male and female individuals from the general population, respectively. The male soccer players were ectomorphic mesomorphs, while the females were balanced mesomorphs, defining a sport-specific morphology. This study provides sex- and role-specific anthropometric standards for elite soccer players. Raw anthropometric reference values may be useful for evaluating body composition without using any predictive equations or assumptions.